Apakah Audit Fee Meningkatkan Kualitas Audit? Sebuah Systematic Literature Review - Muhamad Ivo Nizar Ramadhani (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
This study aims to map the development of research on audit fees and audit quality in Indonesia through a Systematic Literature Review (SLR) approach. The study reviewed 103 articles published in SINTA-accredited national journals during the 2020–2026 period. The articles were analyzed to identify publication trends, methodological characteristics, analytical techniques, variable patterns, and empirical findings regarding the relationship between audit fees and audit quality. The results indicate that research on audit fees and audit quality is still dominated by quantitative approaches with direct testing models, particularly using logistic regression analysis. Empirically, the effect of audit fees on audit quality does not show a fully consistent pattern. Audit fees can positively contribute to audit quality when they reflect increased audit effort, resource allocation, and the expansion of audit procedures. However, the effect may become insignificant or problematic when it is not supported by auditor independence, audit firm reputation, audit committee effectiveness, quality control, and adequate corporate governance. Theoretically, audit fees should be understood as a contingent variable within the frameworks of agency theory, signaling theory, legitimacy theory, and stakeholder theory. These findings suggest that future research should shift from direct relationship testing toward models that explain when, why, and through what mechanisms audit fees influence audit quality.